Combining Energy Networks: The Impact of Europe's Natural Gas Network on Electricity Markets until 2050 - Jan Abrell; Clemens Gerbaulet; Franziska Holz; Casimir Lorenz; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2013)
The interdependence of electricity and natural gas is becoming a major energy policy and regulatory issue in all jurisdictions around the world. The increased role of gas fired plants in renewable-based electricity markets and the dependence on gas imports make this issue particular striking for the European energy market. In this paper we provide a comprehensive combined analysis of electricity and natural gas infrastructure with an applied focus. We analyze different scenarios of the long-term European decarbonization pathways sketched out by the Energy Roadmap 2050, and identify criteria related to electricity and/or natural gas infrastructure and the interrelation between both markets.
Keywords: L94; L95; C61; 330; Europe; electricity markets; natural gas markets; networks; Gasversorgung; Infrastruktur; Energiemarkt; Europa